Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/bdd.1846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of natural phytochemicals in Angelica sinensis (Danggui) on Nrf2‐mediated gene expression of phase II drug metabolizing enzymes and anti‐inflammation

Abstract: The root of Angelica sinensis (Oliv.) Diels (abbreviated as AS) (Danggui) has a long history in Asian herbal medicine. Recently, it was demonstrated that AS possesses anti-cancer and anti-oxidant activities. Because the transcription factor Nrf2 mediates the expression of many cellular anti-oxidative stress genes, including genes that are involved in phase II drug metabolism and anti-oxidative stress, this study sought to investigate whether pure compounds from AS or an AS extract could activate antioxidant re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Z‐Ligustilide is an active ingredient in C. officinale and A. acutiloba and shows several biological activities . In the present study, we investigated the inhibitory effect of Z‐Ligustilide on BaP‐induced CYP1A1 upregulation and its underlying mechanism in cultured human keratinocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Z‐Ligustilide is an active ingredient in C. officinale and A. acutiloba and shows several biological activities . In the present study, we investigated the inhibitory effect of Z‐Ligustilide on BaP‐induced CYP1A1 upregulation and its underlying mechanism in cultured human keratinocytes.…”
Section: Discussionmentioning
confidence: 97%
“…Ma and Bai found that Z-ligustilide significantly inhibited NF- κ B activation and the production of IL-1 β and TNF- α in experimental ovariectomized (OVX) osteopenic rats and endotoxin-induced uveitis rats [49, 50]. Generally speaking, FA and Z-ligustilide, two major compounds in RA, activated the Nrf2 pathway and decreased NF- κ B luciferase activity, which may contribute to the anti-inflammatory activity of RA [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Currently, extracts from Angelica sinensis possess anti-cancer and anti-oxidant activities, which activate the Nrf2 pathway to mediate the expression of many cellular anti-oxidative stress genes, protect organs and tissues against oxidative stress (Saw et al, 2013); extracts from Angelica sinensis can also suppress the growth of malignant brain tumor cells, up-regulate expression of p53 protein, cyclin kinase inhibitors p16, decrease the phosphorylation of Rb proteins, leading to arrest at the G0-G1 phase and activation of apoptosisassociated proteins in p53 pathway, significantly prolong patient survival (Lin et al, 2013). Angelica sinensis can decrease the adhesive, invasive and migratory ability of human lung adenocarcinoma A549 cells, down-regulate the expressions of matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9) at both the protein and mRNA levels, inhibit the enzymatic activity of MMP-2 and MMP-9, possesses anti-growth and antimetastasis activity against lung cancer cells (Gao et al,…”
Section: 4609 Tumor Inhibition By Angelica Sinensis and Sophorae Flamentioning
confidence: 99%